A DEM–FEM coupling based approach simulating thermomechanical behaviour of frictional bodies with interface layer. (1st March 2016) - Haddad, H.; Guessasma, M.; Fortin, J.
Abstract: The behavior of granular flow during a sliding contact is difficult to predict. As observed in the literature, the most commonly used tools for simulating sheared granular flows are the Discrete Element Method (DEM) and Finite Element Method (FEM). This work presents a new numerical methodology for studying the thermomechanical behavior of the contact interface between two bodies subjected to a tribological loading. The numerical model is based on DEM–FEM coupling approach in order to ensure the interaction between the bodies and the transfer film situated in the interface. This modeling has enabled a description of the physical phenomena to be given, in particular thermal transfer, and structure heterogeneities with good accuracy. Numerical tests, carried out in dynamic problems, have demonstrated the capability of the proposed coupling approach to ensure the transition of thermal and mechanical quantities between two scales. Emphasis is still placed on the influence of the mechanical parameters and kinematic conditions on the thermomechanical behavior of the contact interface.